Head Lice Eradication Efforts in a Group Home Environment: Yayasan Griya Asih Orphanage – A Case Study - Natalia Puspadewi; Christian Ardianto; Gisella Anastasia (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
Children living in orphanages are generally vulnerable to close-contact transmission diseases, including head lice infestation. The clinical manifestation of head lice infestation was relatively mild, such as itchy scalp, and hence it is often overlooked as a community health issue. Education plays an essential role in preventing re-infection and eradicating head lice infestation. The treatment options include chemical treatment using pediculicides and physical management by shaving the head and manually removing the parasite. This community service activity aimed to eradicate head lice from Yayasan Griya Asih Orphanage. A series of three activities were conducted at Yayasan Griya Asih Orphanage in Central Jakarta. Each activity was done around one month apart to evaluate the effectiveness of treatment. Firstyear medical students were recruited to participate in these activities to familiarize them with real-world community health problems. Student volunteers helped applied pulse doses of Permethrin 1% shampoo and provided health education activity. Fiftyfive Yayasan Griya Asih Orphanage residents joined this activity from mid-October until December 2022. Residents were instructed not to share their personal items to prevent re-infection. Health education activities were done using one-to-many followed by a one-on-one format. In conclusion, head lice infestation screening is essential in crowded environments, and permethrin 1% pulsed dose followed by personalized health education activities and pest control effectively broke the disease transmission chain and eradicated the head lice infestation.